TEXT STEGANOGRAPHY USING THE SECOND QUOTIENT REMAINDER THEOREM AND DARK COLOUR SCHEMES (Journal of Computational Innovation and Analytics (JCIA), 2023)
Data communication over the Internet has increased significantly, resulting in high data traffic and concerns over data security. Information sent over the Internet always gets the attention of intruders, which causes the effort to increase the security of sensitive data and the need to prevent leakage. Steganography is one of the techniques to protect the confidentiality of data that can be accomplished by hiding secret information within the medium of text, images, audio, and video. Hiding a secret message using text steganography can be done on character properties such as size, colour, style, etc. Colour- based steganography has always raised suspicions about the generated stego text, which is a major issue in this study. Therefore, the Red, Green, and Blue (RGB) colour technique and the Second Quotient Remainder Theorem (SQRT) were introduced in this study to perform the hiding process. RGB (0,0,0) to RGB (15,15,15) colours were used for the hiding process to avoid colour suspicion. In addition, the pseudorandom number generator (PRNG) was also used to generate dynamic hidden messages with Homophonic table generation. The results showed that the secret message can be represented dynamically and has increased the hiding capacity to 77.4%. Other than that, the selected colour has successfully avoided the suspicion of the generated stego text. Hence, the results suggested that SQRT could be employed as a method in text steganography for securing information.